The impact of metazooplankton on the structure of the microbial food web in a shallow, hypertrophic lake - Jürgens, Klaus; Jeppesen, Erik (Journal of Plankton Research, 2000)
Shallow, hypertrophic Lake Søbygård is characterized by strong fluctuations in the plankton community structure over short time scales, and cascading predation effects from higher to lower trophic levels. We examined the coupling between the classical and microbial food web for a 1 month period, during which the typical zooplankton summer succession from rotifers (mainly Brachionus spp.) to cyclopoid copepods and daphnids occurred. In addition to the analysis of the plankton succession, we performed mesocosm experiments, comparing the microbial community structure in treatments with and without metazooplankton. We focused on the development of different functional groups within the microbial food web: total heterotrophic bacteria, filamentous bacteria (as grazing-resistant forms), prokaryotic and eukaryotic, autotrophic picoplankton (pAPP and eAPP), heterotrophic nanoflagellates (HNF) and ciliates. During the first experiment, the metazooplankton was dominated by rotifers which exerted only moderate top-down control on small ciliates, HNF and APP. Cascading predation effects were visible after the collapse of the rotifer population; enhanced protozoan grazing resulted in a decrease in single-celled bacteria and an increase in filamentous bacteria. During the second experiment, characterized by dominance of Cyclops vicinus , strong alterations in the microbial food web structure occurred. The most obvious effects were an efficient predation control of planktonic ciliates by copepods and a shift of the picoplankton towards filamentous bacteria and a very high biomass of pAPP, which we interpret as a result of enhanced protozoan grazing pressure on bacterioplankton. After the peak in cyclopoids, Daphnia spp. became the dominant zooplankton taxa which resulted in the well known strong predation effects on all microbial components. The two experiments confirm that metazooplankton species composition is an important structuring factor for the microbial food web. Two functional groups deserve special attention: ...